2017
DOI: 10.1208/s12249-017-0919-6
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembling Raloxifene Loaded Mixed Micelles: Formulation Optimization, In Vitro Cytotoxicity and In Vivo Pharmacokinetics

Abstract: Raloxifene (RLX) has been strongly recommended for postmenopausal women at high risk of invasive breast cancer and for prevention of osteoporosis. However, low aqueous solubility and reduced bioavailability hinder its clinical application. The objective of this study was to explore the potential of RLX loaded mixed micelles (RLX-MM) using Pluronic F68 and Gelucire 44/14 for enhanced bioavailability and improved anticancer activity on human breast cancer cell line (MCF-7). RLX-MM were prepared by solvent evapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Earlier studies reported an antiproliferative effect of RLX on MCF-7 cells for up to 100 μg/mL in concentration. For instance, pure RLX and RLX-loaded mixed micelles using Pluronic F68 and Gelucire 44/14 exhibited IC 50 values of 94.71 and 22.5 μg/mL, respectively on MCF-7 cells [ 8 ]. Additionally, Kim, D et al reported the use of about 5 μg/mL of RLX to kill 50% of MCF-7 cells within 48 h [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies reported an antiproliferative effect of RLX on MCF-7 cells for up to 100 μg/mL in concentration. For instance, pure RLX and RLX-loaded mixed micelles using Pluronic F68 and Gelucire 44/14 exhibited IC 50 values of 94.71 and 22.5 μg/mL, respectively on MCF-7 cells [ 8 ]. Additionally, Kim, D et al reported the use of about 5 μg/mL of RLX to kill 50% of MCF-7 cells within 48 h [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…RLX has been reported to stimulate gene promoters regulated by ERβ subtype that guards against tumor formation in response to estrogen; therefore, it exhibits anti-tumor activity in breast cancer cells [ 6 ]. Nevertheless, RLX suffers from poor aqueous solubility and exposure to dramatic pre-systemic metabolism that lead to diminished bioavailability that does not surpass 2% [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such changes suggested that the functional groups of geraniol oil were included and interacted with the formulation functional groups. Thus, geraniol oil was successfully encapsulated inside the prepared mixed micelles [31,58], as shown in Figure 3. which means more abundance of O and OH points that enhance attachment to the drug molecule via hydrogen bonds leading to slower release rate [57].…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 97%
“…Such changes suggested that the functional groups of geraniol oil were included and interacted with the formulation functional groups. Thus, geraniol oil was successfully encapsulated inside the prepared mixed micelles [31,58], as shown in Figure 3.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)mentioning
confidence: 97%
See 1 more Smart Citation